Pengembangan Media Pembelajaran Pop Up Book IPA Berbasis Kontekstual untuk Meningkatkan Keterampilan Berpikir Kreatif Siswa SMP - Antika Salma Augeta (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
Students' creative thinking skills in Indonesia are still relatively low, this is because students have difficulty in understanding the material that has been learned, are limited and inhibited in conveying ideas, and the learning process is less efficient because it only uses learning media that is less interesting and uses lecture methods that are easily boring. This study aims to describe the validity, practicality, and effectiveness of contextual-based science Pop Up Book learning media to improve creative thinking skills of junior high school students. Creative thinking skills measured include fluency, flexibility, originality, elaboration. This research uses a development research design with the ADDIE model, namely Analysis, Design, Develop, Implement, and Evaluate. Data collection techniques and instruments used include validation sheets, learning implementation observation sheets, test questions (pre-test and post-test), and student response sheets to measure students' creative thinking skills. The results of data analysis showed that the contextual-based science Pop Up Book media obtained a validity score of 88,28% with very valid criteria. The practicality of the contextual-based science Pop Up Book media through the learning implementation observation sheet obtained a score of 89,14 % with very practical criteria. The use of contextualbased science Pop Up Book media is also proven effective through the results of the N-gain score of 0,56 with moderate criteria. As well as student responses to the contextual-based Science Pop Up Book were very good with a score of 90,05%. The contextual-based science Pop Up Book media developed as a whole can be concluded that it is valid, practical, and effective for improving the creative thinking skills of junior high school students.
Entry oleh Arif 2026 Maret 25
Keywords: Pop Up Book Science Learning Media; Contextual; Creative Thinking Skills